Bile-Esculin Test for Presumptive Identification of Enterococci and Streptococci: Effects of Bile Concentration, Inoculation Technique, and Incubation Time - Chuard, C. (American Society for Microbiology, 1998)
The bile-esculin test is used to differentiate enterococci and group D streptococci from non-group D viridans group streptococci. The effects on test performance of the concentration of bile salts, inoculum, and duration of incubation were examined with 110 strains of enterococci, 30 strains of Streptococcus bovis, and 110 strains of non-group D viridans group streptococci. Optimal sensitivity (>99%) and specificity (97%) of the bile-esculin test can be obtained with a bile concentration of 40%, a standardized inoculum of 10(6) CFU, and incubation for 24 h.